THE CALCULATION OF THERMODYNAMIC PROPERTIES FOR HYDROCHLORIC AND COPPER COMPOUNDS IN A HYDROGEN PRODUCTION PROCESS - Avsec, Jurij; Naterer , Greg F.; Predin, Andrej (Journal of Energy Technology, 2024)
Efficient and sustainable methods of clean fuel production are needed in all countries of the world in the face of depleting oil reserves and the need to reduce carbon dioxide emissions. With commitments for a hydrogen village, a hydrogen airport and a hydrogen corridor, the Canadian province of Ontario has already begun to move toward a hydrogenͲfueled economy. However, a key missing element is a largeͲscale method of hydrogen production. As a carbonͲ based technology, the predominant existing process (steamͲmethane reforming (SMR)) is unsuitable. This paper focuses on a copperͲchlorine (CuͲCl) cycle, and the models of calculating thermodynamic properties. It discusses the mathematical model for computing the thermodynamic properties for pure substances such as H2, CuCl and HCl, which are important inhydrogen production in their fluid phase, with the aid of statistical chain theory. The constants required make this computation, such as the characteristic temperatures of rotation, electronic state etc., and the moments of inertia are obtained analytically, by applying the knowledge of the atomic structure of the molecule. The procedures for calculating essential thermodynamic properties such as pressure, speed of sound, the specific heat, volumetric expansion coefficient, enthalpy and entropy are presented. To calculate the thermodynamic properties of LennardͲ Jones chains, we have used the LiuͲLiͲLu and TangͲLu models. The thermodynamic properties of the LennardͲJones mixtures are obtained using the oneͲfluid theory. In recent years, thermodynamic theories based on statistical thermodynamics have been rapidlydeveloped. Fluids with chain bonding and association have also received much attention. The interest in these fluids is due to the fact that they cover much wider range of real fluids than spherical ones. A good theory for these fluids will be very beneficial for chemical engineering applications, by reducing the number of parameters, and making them more physically meaningful and more predictable. In technical practice, energy processes are of vital importance. In order to design devices in this field of activity, it is necessary to be familiar with the equilibrium and nonequilibrium thermodynamic properties of state in a oneͲand twoͲphase environment for pure refrigerants and their mixtures. To calculate the thermodynamic properties of real fluid, the LiuͲLiͲLu (LLL) (revisited Cotterman) equation of state, based on simple perturbation theory and SAFTͲVR equation of state for LJ chain fluid was applied. We developed the mathematical model for the calculation of all equilibrium thermodynamic functions of state for pure hydrocarbons and theirmixtures. In this paper, we have developed an analytical model based on the statistical thermodynamics and chain theory for pure components such as H2, CuCl and HCl in the fluid region.
Keywords: Hydrogen production; Cu-Cl cycle; thermophysical properties; statistical thermodynamics